Gentilicios africanos en la costa central del Perú, siglo XVII - Cajavilca Navarro, Luis (2005)
Slavery was a cruel way of explotation. However, during the Spanish dominance, a crossbreeding process took place and half-breed and afroperuvian population’nuclei were set. This crossbreeding process was increased in the XVIII centurywhen black people come from African tribes bringing two linguistic groups: Sudanes and Bantu, as well as the use of their words called interlingua.